Performance of region‐of‐influence approach of frequency analysis of extreme rainfall in monsoon climate conditions. (8th March 2017) - Das, Samiran
ABSTRACT: This study investigates the applicability of the region‐of‐influence (ROI) approach of frequency analysis of extreme rainfall in a monsoon‐dominated country and to find the most appropriate scheme of the method. Seven different ROI pooling schemes are examined which differ in their similarly distance measure containing a range of different site descriptors (also known as pooling variables). The site descriptors also include average annual monsoon rainfall (AAMR) which is introduced to assess its suitability in this climatic condition. The ROI schemes are evaluated against traditional regional as well as at‐site frequency analysis. The performance of the selected scheme in terms of homogeneity and frequency behaviour is also assessed. In order to determine the performance, the study uses annual maximum rainfall data of 1‐day duration at 34 stations in Bangladesh, which has a tropical monsoon climate. It is found that the ROI method of any variants is superior to the traditional geographical approach of regional analysis as well as to the at‐site analysis. The AAMR based pooling scheme has provided the best result among the considered ROI schemes. The pooling groups delineated based on AAMR has also passed the homogeneity test and conveyed a desirable frequency behaviour. All results indicate that the AAMR as a pooling variable, i.e. information about monsoon rainfall, should be accommodated to the estimation of extreme rainfall in a monsoon‐dominated region.